Residences Queen's Park Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
A view of two affluent two storey homes located around the Queen's Park Savannah. The tram can also be seen making its way with passengers around the Savannah.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Dwellings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; [1905]; Trees--Trinidad and Tobago; Savannas--Trinidad and Tobago; Street-railroads--Trinidad and Tobago; Architecture--Trinidad and Tobago; Architecture, Domestic--Trinidad and Tobago; Windows--Trinidad and Tobago; Roofs--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)